The Relationship Between the Classroom Management Skills, Self-Efficacy, and Curriculum Literacy Levels of Teachers Working in Special Education Schools - Ünal, Özlem; Kırkıç, Kamil Arif; Kırkıç, Kamil Arif (Erzurum Kültür ve Eğitim Vakfı, 2024)
The significance of special education has been on the rise recently. Considering this trend, there has been a growing interest in studying the abilities and attributes of teachers working in special education institutions. This study explored the connection between classroom management skills, self-efficacy beliefs, and proficiency in curriculum among teachers in special education settings. Employing a correlational, quantitative research model, this study involved 421 teachers from special education schools. The classroom management skills scale, teacher self-efficacy belief scale, and curriculum literacy scale, conducted online in the spring of 2021, were used to collect data. Statistical analyses included Pearson correlation analysis. After calculating the correlation between the variables, multiple regression analyses were employed. The findings revealed a moderate positive correlation among the three variables. Furthermore, it was established that teachers' self-efficacy beliefs and curriculum literacy significantly predicted 38.6% of their classroom management skills. Enhancing teachers' self-efficacy beliefs and curriculum literacy is beneficial for improving their classroom management abilities.

Özel eğitimin önemi son yıllarda artmaktadır. Ortaya çıkan bu durum çerçevesinde, özel eğitim okullarında çalışan öğretmenlerin sahip oldukları beceriler ve özellikler de araştırma konusu olmaktadır. Bu araştırmada nicel araştırma modellerinden korelasyonel model kullanılmıştır. Çalışmaya, özel eğitim okullarında çalışan 421 öğretmen katılmıştır. Veriler Sınıf Yönetimi Becerileri Ölçeği, Öğretmen Özyeterlik İnancı Ölçeği ve Eğitim Programı Okuryazarlığı Ölçeği ile toplanmıştır. Veriler 2021 yılı bahar döneminde online olarak toplanmıştır. Veri analizinde Pearson Korelasyon analizi ve Çoklu Regresyon Analizi kullanılmıştır. Üç değişken arasında pozitif orta düzeyde bir korelasyon olduğu belirlenmiştir. Öğretmen özyeterlik inancı ve eğitim program okuryazarlığı değişkenlerinin özel eğitim öğretmenlerinin sınıf yönetim becerilerinin %38,6’sını yordadığı bulunmuştur. Öğretmenlerin öz-yeterlik inançlarının ve program okuryazarlığının güçlendirilmesi, öğretmenlerin sınıf yönetimi becerilerine katkıda bulunacaktır.
Özel Eğitim Okullarında Çalışan Öğretmenlerin Sınıf Yönetim Becerileri, Öz-Yeterlilik ve Program Okuryazarlık Düzeyleri Arasındaki İlişki
Keywords: Special education; Classroom management skills; Special education teacher; Program literacy; Teacher self-efficacy; Özel eğitim; Özel eğitim öğretmeni; Öğretmen öz-yeterliği; Sınıf yönetimi becerileri; Program okur-yazarlığı